Determination of chlorşmphenlcoi residues in milk collected from some small dairy factories in konya - Ömer Demet; A. Levent Baş; Bünyamin Traş (Eurasian Journal of Veterinary Sciences)
In this study, chloramphenicol residues were studied in sixtyone milk samples collected from small dairy factories in Konya, by HPLC Chlorampenicol was found in twentyeight of the milk samples analysed. The limit level of chloramphenicol determined in milk was 3.10 ng/ml, the highest level was 266.67 ng/ml, the average level was 55.96 ng/ ml.